Thumped ebook - McCafferty, Megan (Bumped, 2012)
Megan McCafferty's Bumped series of books are must-read teen dystopian fiction, along with Ally Condie's Matched series and Veronica Roth's Divergent trilogy. Thumped, the sequel to Bumped, manages to be satiric, scary, and romantic at the same time. It continues the story of separated-at-birth twins, Melody and Harmony, girls as engaging as McCafferty's Jessica Darling. These sisters are the most popular teen girls on the planet. To their fans, they seem to be living ideal lives. Harmony is married to Ram and living in Goodside, the religious community that once meant everything to her. Melody has the genetically flawless Jondoe as her coupling partner, which means money and status—and a bright future. But both girls are hiding secrets. And they are each pining for the only guys they can't have.... The biggest risk of all could be to finally tell the truth.